Answer:
x = 6
Step-by-step explanation:
We want to solve:
![\frac{-2}{3} x+9=\frac{4}{3} x-3](https://tex.z-dn.net/?f=%5Cfrac%7B-2%7D%7B3%7D%20x%2B9%3D%5Cfrac%7B4%7D%7B3%7D%20x-3)
First, isolate the variable by moving all the terms with x to one side and all the constants to the other side:
![\frac{4}{3}x +\frac{2}{3} x=9+3](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7Dx%20%2B%5Cfrac%7B2%7D%7B3%7D%20x%3D9%2B3)
Combining the fraction on the left, we get:
![\frac{6}{3} x=12](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B3%7D%20x%3D12)
6/3 = 2, so:
2x = 12
Dividing both sides by 2 yields:
x = 6
Answer:
y and x are variables, the 5 in 5y is a coefficient so is the 4 in 4x, the 3 is called a constant
Step-by-step explanation:
The answer is C. So if u plug it in the equation should look something like this: 4*12 / 2
25^2=7^2 + x^2
49 + x^2 = 625
x^2= 576
square both sides
x=24
Answer:
The value under the radical is 3
Step-by-step explanation:
9^(2/3) This means 9 squared then find find the cube root of the answer.
9^(2/3)=∛(9^2 )
= ∛81
= ∛(3×3×3×3) = ∛(3)³ ₓ ∛3
= 3∛3
The value under the radical is 3
I hope this now shows clearly the number under the radical is 3.
BRAINLIEST?